A Systematic Literature Review of Micro, Small, and Medium Enterprise (MSME) Development and Management Challenges in Timor-Leste: Opportunities for Sustainable Economic Growth - Cardoso Cardoso; Wahyu Purnomo (International Journal of Economic and Tourism Research, 2026)
Timor-Leste is one of the youngest nations in Southeast Asia and continues to face significant economic and managerial challenges despite substantial development progress since independence in 2002. Micro, Small, and Medium Enterprises (MSMEs) have emerged as a strategic sector for employment generation, poverty reduction, and economic diversification. However, the development of MSMEs in Timor-Leste remains constrained by limited managerial capabilities, inadequate access to finance, weak infrastructure, low levels of innovation, and insufficient institutional support. This study aims to systematically review the existing literature on MSME development and management challenges in Timor-Leste. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach, literature from international journals, government reports, development agency publications, and institutional databases published between 2010 and 2025 were analyzed. The findings indicate that management competency, entrepreneurial education, financial inclusion, digital transformation, and government policy effectiveness are critical determinants of MSME performance. The review further identifies significant research gaps regarding digital entrepreneurship, sustainable business practices, and innovation management within Timorese enterprises. The study contributes to management literature by synthesizing existing evidence and proposing strategic recommendations for policymakers, academics, and practitioners to strengthen the MSME ecosystem in Timor-Leste.